Collaborative research to enable the design of resilient and sustainable systems in the UK built environment and infrastructure sectors - Street, R; ARCC Network (ARCC, 2011)
There is a need to adapt existing dwellings, installations and networks to cope with both today's climate and the likely future climate. This brochure summarises progress to date within the ARCC research programme and aims to inform a range of stakeholders including policy-makers, planners, designers and network operators.